(untitled) (Intent Research Scientific Journal, 2023)
This paper emphasizes how interactive whiteboards may help with English language instruction and acquisition. As language is a means of communication, it is crucial to the development of language learners’ communicative skills. It happens frequently for students to acquire the fundamentals of grammar yet still struggle to talk with assurance in social circumstances. The process of interaction, which involves both input and output, is essential for the growth of a language’s communication abilities. In contrast to a simple whiteboard, the interactive whiteboard may improve contact between teachers and students as well as among learners because its primary role is interactivity. As a result, it may be a useful tool for teaching English.